Design of a Constant Current Laser Driver for Biomedical Applications - Temel, Ozgur Deniz; Ferhanoglu, Onur; Yelten, Mustafa Berke (IEEE, 2021)
In this paper, an integrated constant current laser driver has been designed for biomedical engineering applications, along with an extra reference generator for nearby circuit blocks in the system using the same circuit core. The designed laser driver achieves a continuous wave operation for a vertical-cavity surface-emitting laser (VCSEL) by supplying a current of 12 mA. The reference current source provides a current of 95 µA. The total power consumption of both circuits is 49.4 mW. Monte Carlo analysis has been performed and the operation of both current references have been ensured despite a 3σ process parameter variation.